Diode-Pumped Single-Longitudinal-Mode Pr3+:YLF Laser Based on Combined Fabry–Perot Etalons at 522.67 nm - Weicheng Dai; Haozhu Wang; Long Jin; Chang Liu; Yuan Dong; Guangyong Jin (Photonics, 2023)
We create a rate equation theoretical model of a continuous-wave end-pumped Pr3+:YLF SLM laser that characterizes the output properties of a single-longitudinal-mode (SLM) green laser. After inserting two Fabry–Perot (F–P) etalons with thicknesses of 0.3 mm and 0.5 mm and angles of 1.42° and 0.69° into the cavity, a single-longitudinal-mode green laser was generated. The maximum output power in single-longitudinal mode was 183 mW. The maximum absorbed pump power was 6.2 W. The corresponding linewidth is about 18 MHz. This work presents a simple method for generating a single-longitudinal-mode laser in the green spectral region, providing a practical approach for various green-laser-related applications.